Colonialism in the margins : cultural encounters in New Sweden and Lapland - Fur, Gunlög Maria (Atlantic world (Leiden, Netherlands), 2006)
This book explores Swedish encounters with American Indians in the New Sweden colony on the Delaware River during the second half of the seventeenth century. To place Swedish-Indian interactions in perspective, a comparison is made with Swedish-Saami colonial relations during the same time period. These were two expressions of Great Power ambitions that place Sweden firmly within the context of European colonialism, but also meant the two outstanding examples of Swedish encounters with indigenous populations. Focus is on issues of land ownership and transactions, on trade, and on cultural encounters. The book is of particular interest to historians of colonial encounters in America and Sweden, but also in a larger context concerning European colonialism and its heritage today.